Laboratory Diagnostic Options and Challenges for Chikungunya Viruses - Rahman, MM (Pulse, 2018)
Background: Chikungunya infection is a Aedes mosquito transmitted viral disease caused by Chikungunya virus (CHIKV), a member of the Alphavirus genus. It is an important human pathogen that causes a syndrome characterized by fever, chills, headache and severe joint pain usually of the smaller joints, with or without swelling. Though the disease is almost self-limiting, during the recent outbreak CHIKV was also found to cause long-term arthralgia, neurological disease and even few fatalities. Despite the fact that CHIKV is associated with epidemics of unprecedented magnitude, only a few specific serological and molecular diagnostic tools are available. Objective: CHIKV diagnosis is essentially based on virus isolation, reverse transcription (RT)-PCR and ELISA assays. The gold standard of CHIKV diagnosis is culture, however, required facilities and skills are not available in any routine laboratory in the country. Highly sensitive and specific PCR assays for CHIKV have been developed and commercially available. Conclusion: Although the reagents and equipment are costly for widespread use RT-PCR is the method of choice for the early detection and confirmation of virus in clinical samples as most acutely infected patients seek medical attention within the first few days of illness when role of serology based diagnosis is minimum. Pulse Vol.10 January-December 2017 p.18-24